Kegiatan Layanan Ruang Baca Anak di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Septasia, Elsha Yuan; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this paper is to describe (1) a service activity exists in the library of Bung Hatta Bukittinggi, especially in reading room; (2) the constraints of service in the children's reading room in UPT Perpusatkaan Proklamator Bung Hatta Bukittinggi. The Data collected through observations, interviews and literature study. The findings of this research is based on analysing school financing data can be concluded as follows: (1) children's services has not been in accordance with the existing services namely tutoring services in reading, reading, children's referral service, storytelling, film and performances; (2) the complete lack of infrastructure; (3) the less human resources. Keywords: reading room; child care